DEVELOPING FRAMEWORK FOR IMPROVING DISASTER RESILIENCE IN URBAN SLUM UPGRADING - Tauhid, Fahmyddin A'raaf (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2019)
Abstract_ Disaster resilience has become an important urban agenda due to the increasing disaster intensity and massive impacts. Developing framework for measuring disaster resilience is a critical policy particularly for urban slum area. It requires extensive and comprehensive approach to achieve sustainable measurement. Providing the integration of the research and the present disaster resilience measurement through content analysis of qualitative approach, this study introduces the framework composed of categories and indicators for improving disaster Resilience in urban slum areas under upgrading efforts. It recommends that community capital: the public infrastructure and facilities, human, financial, natural, and social can be categories for indicators development. These capitals can reflect numerous elements, resources, and relationships within an urban slum areas and its main contribution for community.Keywords: Disaster Resilience; Slum Upgrading; Community Capital.